Synaptic proteome perturbations after maternal immune activation : Identification of embryonic and adult hippocampal changes - Yotova, Anna Y.; Li, Li-Li; O’Leary, Aet; Tegeder, Irmgard; Reif, Andreas; Courtney, Michael J.; Slattery, David A.; Freudenberg, Florian (Academic Press, 2025)
Background
Maternal immune activation (MIA) triggers neurobiological changes in offspring, potentially reshaping the molecular synaptic landscape, with the hippocampus being particularly vulnerable. However, critical details regarding developmental timing of these changes and whether they differ between males and females remain unclear.
Methods
We induced MIA in C57BL/6J mice on gestational day nine using the viral mimetic poly(I:C) and performed mass spectrometry-based proteomic analyses on hippocampal synaptoneurosomes of embryonic (E18) and adult (20 ± 1 weeks) MIA offspring.
Results
In the embryonic synaptoneurosomes, MIA led to lipid, polysaccharide, and glycoprotein metabolism pathway disruptions. In the adult synaptic proteome, we observed a dynamic shift toward transmembrane trafficking, intracellular signalling cascades, including cell death and growth, and cytoskeletal organisation. In adults, many associated pathways overlapped between males and females. However, we found distinct sex-specific enrichment of dopaminergic and glutamatergic pathways. We identified 50 proteins altered by MIA in both embryonic and adult samples (28 with the same directionality), mainly involved in presynaptic structure and synaptic vesicle function. We probed human phenome-wide association study data in the cognitive and psychiatric domains, and 49 of the 50 genes encoding these proteins were significantly associated with the investigated phenotypes.
Conclusions
Our data emphasise the dynamic effects of viral-like MIA on developing and mature hippocampi and provide novel targets for study following prenatal immune challenges. The 22 proteins that changed directionality from the embryonic to adult hippocampus, suggestive of compensatory over-adaptions, are particularly attractive for future investigations.